The relative contribution of psychological barriers to the cognitive load of university students - Abdel-Latif, Mohamed Sayed Mohamed; Abdel-Gawad, Mervat Azmy Zaki (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the relationship between psychological barriers and the cognitive load among Prince Sattam bin Abdulaziz University students who use the e-learning management system (BlackBoard) and to identifying the extent to which psychological barriers degrees contribute in predicting the degrees of perceived cognitive load, For data collection, the analytical descriptive approach was used the researchers applied the psychological barriers scale and the perceived cognitive load scale prepared by the researchers. Results revealed the following: There was a statistically significant positive correlative relationship between the psychological barriers, its' dimensions, the intrinsic, the extraneous perceived cognitive load and the total degree of cognitive load of university students, while there was no correlative relationship between psychological barriers, its' dimensions and the Germane perceived cognitive load of university students. The second axis (the external psychological barriers) was better in predicting the overall degree of perceived cognitive load, and that the arrangement of the sub-dimensions of external psychological barriers in terms of their ability to predict the overall degree of the perceived cognitive load was in the following order: realizing rumors, fear of negative evaluation, and expecting failure. There were no statistically significant differences between male and female university students and between the scientific and literary disciplines in psychological barriers and their dimensions, there were statistically significant differences between male and female university students in intrinsic, extraneous cognitive load and the overall degree in favor of female students. And there were differences between the scientific and literary disciplines in the intrinsic and extraneous perceived cognitive load, and the overall degree of the cognitive load in favor of the literary disciplines. there were no differences between male and female students and between the scientific and literary disciplines in Germane cognitive load.
Keywords: Psychological barriers; Cognitive load; Distance e-learning; Prince Sattam bin Abdulaziz University; Blackboard system